Synthesis of Phosphoryl-Substituted Benzimidazo[2,1-a]isoquinolin-6(5H)-ones from 2-Arylbenzoimidazoles and Diarylphosphine Oxides - Sun, Kai; Si, Ya-Feng; Chen, Xiao-Lan; Lv, Qi-Yan; Peng, Yu-Yu; Qu, Ling-Bo; Yu, Bing (Asian journal of organic chemistry, 2019)
An efficient and convenient silver-catalyzed procedure was developed for the synthesis of various phosphoryl-substituted benzimidazo[2,1-a]isoquinoline-6(5H)-ones from diarylphosphine oxides and 2-arylbenzoimidazoles. Moreover, the phosphoryl-substituted indolo[2,1-a]isoquinolin-6(5H)-ones could also be achieved by using this strategy under mild reaction conditions in the presence of AgNO3/K2S2O8.